Alla ricerca di un nuovo schema mentale (Appunti utili anche per la linea editoriale di "Annali di Storia dell’Esegesi" nei prossimi anni) - Pesce, Mauro (Annali di storia dell' esegesi, 2023)
If my observations in this article are adequate to what is happening, we are facing a world in transformation, in transition. A complex world made up of many factors whose overlapping and crossing creates novelty. The purpose of these pages was twofold: to invite to ask oneself whether one’s research is determined by mental schemes that respond to conditions of the past (thus making it ineffective for the present and for the future); to invite to raise questions about the transformations necessary for future researches on the history of Christianity in the context of a transition to a new era.